2016
DOI: 10.1590/01047760201622021969
|View full text |Cite
|
Sign up to set email alerts
|

Micorrizas Arbusculares No Crescimento De Leguminosas Arbóreas Em Substrato Contendo Rejeito De Mineração De Carvão

Abstract: MICORRIZAS ARBUSCULARES NO CRESCIMENTO DE LEGUMINOSAS ARBÓREAS EM SUBSTRATO CONTENDO REJEITO DE MINERAÇÃO DE CARVÃORESUMO: O objetivo desse trabalho foi avaliar o efeito da inoculação de fungos micorrízicos arbusculares (FMA) no crescimento, colonização micorrízica e absorção de P e elementos-traço em leguminosas arbóreas expostas a rejeito de mineração de carvão. Ensaios independentes para as leguminosas Mimosa scabrella Benth. (bracatinga), Mimosa bimucronata (DC.) Kuntze (maricá) e Parapiptadenia rigida (Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
(12 reference statements)
0
3
0
4
Order By: Relevance
“…The importance of mycorrhizal fungi inoculation in relation to plant growth in mining substrates which present poor, degraded and often contaminated environments becomes remarkable (STOFFEL et al, 2016). The inoculation of arbuscular mycorrhizal fungi generally promotes an increase in height of seedlings/plants in mining substrates, as observed for sabiá (Mimosa caesalpinifolia) seedlings in manganese mining substrate with the inoculation of Glomus etunicatum (GARCIA et al, 2016), in Acacia mangium, Mimosa caesalpiniaefolia and Schinus terebinthifolius forest species with the inoculation of mycorrhizal fungi of the Glomus clarum, Glomus intraradices and Gigaspora rosea species in an area degraded by cassiterite (MENDES et al, 2009), and in Acacia mangium seedlings with AMF inoculation in manganese contaminated substrate/soil (BECERRIL et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of mycorrhizal fungi inoculation in relation to plant growth in mining substrates which present poor, degraded and often contaminated environments becomes remarkable (STOFFEL et al, 2016). The inoculation of arbuscular mycorrhizal fungi generally promotes an increase in height of seedlings/plants in mining substrates, as observed for sabiá (Mimosa caesalpinifolia) seedlings in manganese mining substrate with the inoculation of Glomus etunicatum (GARCIA et al, 2016), in Acacia mangium, Mimosa caesalpiniaefolia and Schinus terebinthifolius forest species with the inoculation of mycorrhizal fungi of the Glomus clarum, Glomus intraradices and Gigaspora rosea species in an area degraded by cassiterite (MENDES et al, 2009), and in Acacia mangium seedlings with AMF inoculation in manganese contaminated substrate/soil (BECERRIL et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Formular mecanismos no jogo que sejam relacionados com o ecossistema local é uma maneira de trazer novas informações de forma dinâmica para as crianças (MIRANDA, 2001), bem como para promover a construção do conhecimento científico sobre determinado ecossistema de forma agradável para os discentes (MENEZES et al 2016). O conhecimento sobre o reino Fungi é um tema desafiador na educação básica, pois esse grupo é formado de espécies macroscópicas e microscópicas, com taxonomia variável que ainda não está totalmente elucidada e devido também à complexidade e diversidade das estruturas morfológicas e reprodutivas dos diversos grupos (STOFELL et al 2016).…”
Section: Jogos Educativos Para O Conhecimento Da Biodiversidade E Ecounclassified
“…A study conducted by Stoffel et al . () demonstrated the ability of young saplings to settle in soil containing coal mining tailings, with the addition that those saplings had the capacity to retain As, Cd, Cr, Cu and Zn in their shoots.…”
Section: Introductionmentioning
confidence: 99%
“…During its growth, bracatinga also stimulates microbial life in the soil, due to the large amount of nitrogen it incorporates and by the accumulation of organic matter (Poggiani et al 1987). A study conducted by Stoffel et al (2016) demonstrated the ability of young saplings to settle in soil containing coal mining tailings, with the addition that those saplings had the capacity to retain As, Cd, Cr, Cu and Zn in their shoots.…”
Section: Introductionmentioning
confidence: 99%